Implementation of communicative language teaching lessons in third graders at Atanasio Girardot sede Sebastián de Belalcázar : a narrative experience (2016)
This research project emerges by applying communicative lesson in English as foreign language for basic elementary. This paper reflects on how using a Communicative Language Teaching and interactive learning can improve the communication through strategies such as pair work based on dialogues, short poem reading, building vocabulary, and speaking. This study focuses on the narrative design, and frames the practitioner research into the descriptive tradition. The Research Tradition selected is the descriptive tradition, because it responds to the investigative requirements for this type of project, which is focused in producing both qualitative and quantitative accounts of processes in the classroom and cultural phenomena; from the perspective of one who participates in the studied context, reflecting on the viewpoints of the participants. Some samples about the student’s behaviors in the class during the teacher develop of the activities were taken by the author. The research questions talk about the process that the learning communities try to provide spaces for speaking English. The general objective describes how English teaching and learning occur under the parameters of communicative language teaching (CLT) in a group of third graders at Atanasio Girardot School.